Pengaruh Curah Hujan terhadap Kualitas Air Sungai Way Kuripan sebagai Sumber Air Baku Perusahaan Daerah Air Minum (PDAM) Way Rilau - Ismadi Raharjo; Iskandar Zulkarnain; Suprapto Suprapto (Jurnal Ilmiah Teknik Pertanian - TekTan, 2013)
So far almost 30%  people need clean water of urban city in Bandar Lampung supplied by PDAM Way Rilau. There are about 12 sources of raw water consisting of surface water , ground water, and springs are treated by PDAM Way Rilau. One source  of raw water is surface water from Way Kuripan processed in "Water Treament Plant (WTP I and WTP II). Therefore,as a surface water, the source of raw water from Way Kuripan is always influenced by external conditions, especially rainfall this study was conducted in early 2013 to take on secondary data consisting of raw water quality parameters: turbidity, degree of acidity (pH), total hardness , dissolved content of Cl, SO 4, KMnO 4, Ca, and Mg are derived from the "PDAM Raw Water analysis Report" for the year 2012; While rainfall data taken from Lampung State Polytechnic Climatology Station which includes parameters: Number of Monthly rainfall , Number of Days Rain, and Rain Maximum every month. Raw water quality parameters of river Way Kuripan highly influenced by rainfall is turbidity, in addition to the content of sulfate and dissolved clorida. In the year 2012 recorded the highest raw water turbidity of 79.1 NTU in December with the condition number of monthly rainfall 354.2 mm, 22 days rainfall, and the maximum daily rainfall of 57.0 mm. However, all of the raw water parameters recorded in the year 2012 is still below the threshold of water-based Group B Regulation  in PP No 82 Tahun  2001.  Because of the quality of raw water from the Way Kuripan strongly influenced by rainfall, especially for turbidity parameters, it is necessary to increase the dose of coagulant is more during the rainy season from December to April. Keywords: raw water, rainfall, water quality, turbidity